2010
DOI: 10.1007/s10514-010-9192-1
|View full text |Cite
|
Sign up to set email alerts
|

Reliable non-prehensile door opening through the combination of vision, tactile and force feedback

Abstract: Whereas vision and force feedback -either at the wrist or at the joint level -for robotic manipulation purposes has received considerable attention in the literature, the benefits that tactile sensors can provide when combined with vision and force have been rarely explored.In fact, there are some situations in which vision and force feedback cannot guarantee robust manipulation. Vision is frequently subject to calibration errors, occlusions and outliers, whereas force feedback can only provide useful informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…hybrid force/position [22] or hybrid force/vision [20] control. This approach was recently extended in a framework integrating vision, force and tact to realize physical interaction tasks [32]. We hereby recall the formulation of that approach, and propose a more generic one, based on classic inverse kinematics control [28].…”
Section: Control Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…hybrid force/position [22] or hybrid force/vision [20] control. This approach was recently extended in a framework integrating vision, force and tact to realize physical interaction tasks [32]. We hereby recall the formulation of that approach, and propose a more generic one, based on classic inverse kinematics control [28].…”
Section: Control Frameworkmentioning
confidence: 99%
“…Let us now compare (5) with the hybrid sensors control used in numerous works [20,22,23,32]. This approach consists in assigning each sensing modality to a Cartesian direction in the operational space, and then summing the velocities associated with the selected sensors:…”
Section: Control Frameworkmentioning
confidence: 99%
“…The relative velocity in the tangential direction of the contact plane can be obtained as follows:ṡ t =ṡ −ḋn P ij (6) Contact forces are described using the soft contact approach which allows small penetration between contacting bodies taking into account local deformations. The amount of this penetration is calculated accordingly with the maximum penetration defined for each sensor.…”
Section: Contact Force Modelmentioning
confidence: 99%
“…In reactive control, the robot has to cope with the inaccuracy of the vision systems when working in unstructured environments [4,5,6]. Recent studies have also shown how tactile-sensing-based algorithms can be employed to detect and react to contacts encountered during the execution of a grasp [7] as well as how tactile sensor information can be used to infer knowledge about grasp stability [8].…”
Section: Introductionmentioning
confidence: 99%
“…Kobayashi, et al [20] applied an IP camera and IR distance sensors to calculate the position of the handle, which could be cylindrical with its diameter 48 mm to 56 mm or lever type. However, vision systems are frequently subject to calibration errors, occlusions and sight ranges, making it inevitable for scholars to apply force sensing to additionally double-confirm the contact position with the handle [21][22][23]. In fact, it is completely competent for robots to use only force sensing to detect the positional relationship with the door and the handle by touching at different positions and different directions, just like humans acting in the darkness.…”
Section: Introductionmentioning
confidence: 99%